EKSISTENSI ILMU FARAIDH UNTUK MENINGKATKAN PEMECAHAN MASALAH BERDASARKAN KEMAMPUAN MATEMATIS MAHASANTRI MA’HAD ALY - Annisaul Qoyyimah; Mohammad Tohir; Muhasshanah Muhasshanah (LP2M Universitas Ibrahimy, 2025)
This study aims to investigate the impact of Faraidh science on improving problem-solving skills among Ma'had Aly students, with a focus on their mathematical abilities. This type of research employs mixed-methods research with a convergent parallel design. The subjects in this study were 30 Ma'had Aly students’. The quantitative data collection technique utilised a mathematical ability test instrument, while qualitative data were obtained through class observations and interviews. The data analysis technique for quantitative research utilizes an instrument test in the form of descriptive statistics and ANOVA tests, while the data analysis technique for qualitative research employs the Miles and Huberman theory, which includes three stages: data reduction, data display, and conclusion drawing and verification. The quantitative results show that the average score of mathematical ability for students is 76.30, with a standard deviation of 6.686. The results of the ANOVA test indicate an F-value of 78.562, with a significance level of p = 0.000. Qualitative data support this finding by showing that contextual and applicable Faraidh science learning improves students' motivation and numeracy skills. This finding confirms that Faraidh science is not only a Sharia science but also serves as an effective medium in developing the mathematical abilities of students. Recommendations for developing more integrative learning methods are presented to optimise learning outcomes.